Experimental Study of The Influence of Tax Knowledge and Tax Attitude on The Performance of Jember District Tax Volunteers - Adilah Fauza; Diyah Probowulan; Achmad Syahfrudin Zulkarnnaeni (West Science Accounting and Finance, 2024)
This experimental research aims to fill the knowledge gap by investigating how taxation knowledge, and taxation attitudes through special treatment and intervention, as well as the provision of training, can affect the knowledge gap. and special interventions, as well as the provision of training whether it can affect the performance of tax volunteers and to prove empirically the differences in Tax Knowledge and Tax Attitude between the experimental group and control group. Theory of Planned Behavior used in this study and with the laboratory experiment model used in this study, the virtual laboratory is a laboratory experiment, the model used in this study, virtual laboratory is a laboratory experiment to be carried out using existing technology. laboratory experiment to be carried out using existing technology, defined as a learning space for virtual experiments. Experimentation is the method used in this study, which is using the type of True Experiment, to be more precise, namely True Experiment Posttest Only Design with Random Assignment, this type of method as well as the novelty of the variables under This type of method as well as the novelty of the variables studied became novelty in this study. Research results, The results of this study indicate that there are differences in taxation knowledge and attitudes towards taxation between the taxation attitudes between the experimental group that received video treatment as training media and the control group that received video as a training media and the control group that did not receive any treatment.